1991
DOI: 10.1139/b91-331
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of two Sphagnum species to photoperiod

Abstract: Growth of two Sphagnum species, S. magellanicum Brid. and S. papillosum Lindb., was studied in the laboratory, field, and greenhouse in relation to photoperiod. Short days (less than 10 h light) induce both species into dormancy. Both species exhibit a high correlation of growth in length and biomass with photoperiod, having maximum length and biomass increase under continuous illumination. Likewise, the ability to lower pH increases with photoperiod. The greater increase in biomass of S. papillosum under 18-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This is consistent with the projection of increased precipitation for much of North America [64] and a positive response of plant productivity to warmer temperatures when moisture is not limiting [65]. Indeed, Sphagnum growth increases with warming and photoperiod [42], [66]. The models therefore suggest that warming would be effectively balanced by precipitation in places where Sphagnum peatlands typically occur.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with the projection of increased precipitation for much of North America [64] and a positive response of plant productivity to warmer temperatures when moisture is not limiting [65]. Indeed, Sphagnum growth increases with warming and photoperiod [42], [66]. The models therefore suggest that warming would be effectively balanced by precipitation in places where Sphagnum peatlands typically occur.…”
Section: Discussionsupporting
confidence: 81%
“…The effect of day length and night temperature on induced frost tolerance Detection of, and reaction to, variation in day length and night temperature are important for plants to survive cold climates (Sakai and Larcher 1987;Li and Glime 1991;Steindal et al 2015). Our winter temperature experiment showed that both day length and night temperature before the onset of freezing have an effect on the freezing tolerance in Sphagnum (Figure 7).…”
Section: Hardening and Responses To Winter Conditions In Relation To mentioning
confidence: 78%
“…The ability of plants to resist external stress is often closely related to the activity of enzymatic defense systems such as SOD, POD, and CAT, which can transform O 2 − and H 2 O 2 into less active substances and reduce or eliminate their ability to attack membrane lipids, thus protecting membrane lipids from oxidation [49,50]. In our study, the activities of SOD, POD, and CAT increased significantly in the Na + Si0 treatment compared to the control (Figure 4).…”
Section: Discussionmentioning
confidence: 99%